2004
DOI: 10.1515/cclm.2004.263
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia is associated with uveitis but not with deep venous thrombosis in Behçet's disease

Abstract: Plasma homocysteine was assessed in Behcet's disease (BD) patients in order to determine the prevalence of hyperhomocysteinaemia in BD and to test its association with clinical manifestations of the disease. The study included 59 patients with BD and 118 age- and sex-matched healthy subjects. Plasma homocysteine, vitamin B(12) and folate were assessed by automated immunoassay methods. Hyperhomo-cysteinaemia was defined as plasma homocysteine >15 micromol/l. Plasma homocysteine concentrations and the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…However, the association between hcy and thrombosis remains statistically significant in many of the studies that considered in the analysis the impact of other potential risk factors, such as male sex or smoking habits. 8,12,25,[27][28][29][30]32,34,35 Furthermore, hcy appeared to be a risk factor for thrombosis even in the 2 studies in which immunosuppressive therapy had been withdrawn before measurement. 28,36 Third, 3 studies 4,25,28 have included also some patients with aneurysms as vascular manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between hcy and thrombosis remains statistically significant in many of the studies that considered in the analysis the impact of other potential risk factors, such as male sex or smoking habits. 8,12,25,[27][28][29][30]32,34,35 Furthermore, hcy appeared to be a risk factor for thrombosis even in the 2 studies in which immunosuppressive therapy had been withdrawn before measurement. 28,36 Third, 3 studies 4,25,28 have included also some patients with aneurysms as vascular manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies were therefore included in our systematic review. 4,7,11,24 -36 The studies performed by Houman et al 35 and Feki et al 34 may have considered in part the same population. However, both the studies were included in our metaanalysis because they considered different end points (Feki et al measured mean hcy levels, and Houman et al assessed the presence of hyperhomocysteinemia).…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Hyperhomocysteinaemia was significantly higher in our male patients. It was found in the studies of Ates et al [18] and Feki et al [23]. These studies are summarized in Table 5.…”
Section: Discussionmentioning
confidence: 85%
“…Our present results showed that serum tHcy levels and HHCY were higher in the active patients than those of the inactive patients and the control subjects. It was demonstrated by Feki et al [23], Ates et al [18], Sarican et al [21], and Aksu et al [13]. …”
Section: Discussionmentioning
confidence: 97%
“…Hyperhomocysteinemia was related to male gender, disease severity, and uveitis. The association between uveitis and hyperhomocysteinemia persisted after adjusting for gender, age, disease activity and duration, smoking, deep venous thrombosis, and serum concentrations of creatinine, vitamin B 12 , and folate [30].…”
Section: Pathogenesismentioning
confidence: 88%